A database of marine and terrestrial radiogenic Nd and Sr isotopes for tracing earth-surface processes - C. L. Blanchet; C. L. Blanchet (Earth System Science Data, 2019)
The database presented here contains radiogenic neodymium and strontium isotope ratios measured on both terrestrial and marine sediments. The main purpose of this dataset is to help assess sediment provenance and transport processes for various time intervals. This can be achieved by either mapping sediment isotopic signature and/or fingerprinting source areas using statistical tools. The database has been built by incorporating data from the literature and the SedDB database and harmonizing the metadata, especially units and geographical coordinates. The original data were processed in three steps. Firstly, specific attention has been devoted to providing geographical coordinates to each sample in order to be able to map the data. When available, the original geographical coordinates from the reference (generally DMS coordinates) were transferred into the decimal degrees system. When coordinates were not provided, an approximate location was derived from available information in the original publication. Secondly, all samples were assigned a set of standardized criteria that help split the dataset into specific categories. For instance, samples were distinguished according to their location (“Region”, “Sub-region” and “Location” that relate to locations at continental to city or river scale) or the sample type (terrestrial samples – “aerosols”, “soil sediments”, “river sediments”, “rocks” – or marine samples – “marine sediment” or “trap sample”). Finally, samples were distinguished according to their deposition age, which allowed us to compute average values for specific time intervals. Graphical examples illustrating the functionality of the database are presented and the validity of the process was tested by comparing the results with published data. The dataset will be updated bi-annually in order to add more data points to increase the sampling density or provide new types of samples (e.g. seawater signature) and/or integrate additional information regarding the samples. It is publicly available (under CC4.0-BY Licence) from the GFZ data management service at https://doi.org/10.5880/GFZ.4.3.2019.001.